The Investigation of the Adsorption of Methylene Blue from Water by Torrefied Biomass - Mariana Consiglio Kasemodel; Leandro Gonçalves de Aguiar; Valéria Guimarães Silvestre Rodrigues; Érica Leonor Romão (Colorants, 2025)
This research investigates the adsorption potential of four types of adsorbents produced from agro-industrial waste (grape pomace—GP, tree pruning—TP, sugarcane bagasse—SB, and eucalyptus sawdust—ES) for the uptake of thiazine dye methylene blue (MB) from aqueous solution. A kinetic model based on a hybrid-order rate equation was fitted to experimental data. The result showed that BGP-300 presented the highest mass yield (58.84%) and energy yield (69.56%), followed by BTP-300 > BES-300 > BSB-300. Adsorption studies showed that BGP-300 had a better performance in the uptake of MB, with a removal efficiency (Re) of 96.5% and adsorption capacity at equilibrium (qe) of 9.3 mg g−1, followed by tree pruning biochar (BTP-300), with an Re of 65.0% and qe of 5.3 mg g−1. Meanwhile, eucalyptus sawdust (BES-300) and sugarcane bagasse (BSB-300) biochar did not facilitate any significant removal of MB. Adsorption kinetics is best described by a second-order rate with R2 varying from 0.75 to 0.96. Desorption studies show a low concentration released to the solution, indicating that adsorption may occur physically and chemically. Therefore, this research provides comprehensive insights into the adsorption characteristics of different biochars, emphasizing the potential of torrefied materials BGP-300 and BTP-300 as effective for MB uptake from aqueous solution.